Effect of Vibration Frequency on Serratus Anterior Muscle Activity during Performance of the Push-up Plus with a Redcord Sling - Yoo, Won-gyu; Kim, Eui-ryong; Oh, Jae-seop (Journal of Physical Therapy Science, 2014)
[Purpose] We investigated the effect of vibration at various frequencies on serratus anterior (SA) muscle activity. [Subjects] Ten male subjects were recruited. [Methods] The subjects performed the push-up plus exercise supported by straps above the surface and vertical ropes in the Redcord sling. During the push-up plus, vibrations of 0, 30, 50, or 90 Hz were applied to the Redcord sling using a mechanical vibration apparatus attached to the rope. SA muscle activity was recorded using electromyography. [Results] SA muscle activity at the 50 Hz vibration frequency was significantly higher than that of no vibration. [Conclusion] Performing the push-up plus using a Redcord sling with mechanical vibration of 50 Hz effectively increased SA muscle activity.